2013
DOI: 10.4161/hv.26335
|View full text |Cite
|
Sign up to set email alerts
|

Seroprevalence of pertussis in China

Abstract: Pertussis remains an important cause of infant death worldwide and is an ongoing public health concern even in countries with high vaccination coverage. A cross-sectional seroepidemiological study was undertaken to estimate true incidence rates and gain further insight into the epidemiology and burden of pertussis in China. During 2011, a total of 1080 blood samples were obtained from healthy individuals between 0 and 86 y of age in Zhengzhou, Central China. Serum IgG antibodies against pertussis toxin (PT) an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
24
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(28 citation statements)
references
References 45 publications
(64 reference statements)
1
24
1
Order By: Relevance
“…We found that 4.3% of subjects not vaccinated with Tdap in the last 6 months had serologic evidence of recent pertussis infection, and that the annual pertussis infection rate among subjects not vaccinated in the last 5 years was 10.5–17.5%. This rate is 1000-fold higher than the annual incidence of reported cases for the general U.S. population in 2014 20 , consistent with other seroprevalence studies that have found pertussis to be vastly underreported 15,18,19 . It is also 10-fold higher than the seroprevalence rate reported from a study among healthy American adolescents and adults in 1997–1999 4 .…”
Section: Discussionsupporting
confidence: 85%
See 2 more Smart Citations
“…We found that 4.3% of subjects not vaccinated with Tdap in the last 6 months had serologic evidence of recent pertussis infection, and that the annual pertussis infection rate among subjects not vaccinated in the last 5 years was 10.5–17.5%. This rate is 1000-fold higher than the annual incidence of reported cases for the general U.S. population in 2014 20 , consistent with other seroprevalence studies that have found pertussis to be vastly underreported 15,18,19 . It is also 10-fold higher than the seroprevalence rate reported from a study among healthy American adolescents and adults in 1997–1999 4 .…”
Section: Discussionsupporting
confidence: 85%
“…Similarly, an Israeli seroprevalence study of subjects at least three years of age demonstrated peak incidence rates in subjects >60 years old, despite this age group having the lowest incidence of reported pertussis cases 21 . Further, a Chinese seroprevalence study in subjects 4–86 years old revealed peak incidence of pertussis in the 31–40 followed by the 41–60 year old age groups 18 . Studies among U.S. adult and adolescent subjects with cough illness suggest 13–15% of these illnesses can be attributed to pertussis 22,23 .…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…However, others have reported highest seropositivity rates in various younger adult age groups [21, 24] or little variation by age among adults [25]. Similarly, some previous studies have reported a possible link between likely pertussis infection and advancing age [20, 22, 31], but others have reported no such link [25, 34, 35]. Whether these results are indicative of true differences between countries and/or years or whether they are due to a lack of sufficient power to detect such differences is unclear.…”
Section: Discussionmentioning
confidence: 99%
“…Higher male seropositivity has also been reported in studies from Mexico ( p  = .0007) [24] and Korea ( p  = .023) [23]; but studies from Spain [26], Greece [21], and The Gambia [22] have reported no significant differences in seropositivity between genders. Regarding higher male likelihood of recent infection, this has been reported to be significant in a study from The Netherlands [31], non-significant in a study from Denmark [34], higher but significance not reported in one from The Gambia [22], or no significant gender differences in two studies from China [35, 36]. Overall, it is unclear whether there is a true link between pertussis and gender and, if there is, the cause is unknown.…”
Section: Discussionmentioning
confidence: 99%